Multi‐omics analyses reveal stone cell distribution pattern in pear fruit. (19th January 2023) - Gong, Xin; Qi, Kaijie; Chen, Juanli; Zhao, Liangyi; Xie, Zhihua; Yan, Xin; Khanizadeh, Shahrokh; Zhang, Shaoling; Tao, Shutian
SUMMARY: Stone cells are the brachysclereid cells in pear ( Pyrus ) fruit, consisting almost entirely of lignified secondary cell walls. They are distributed mainly near the fruit core and spread radially in the whole fruit. However, the development of stone cells has not been comprehensively characterized, and little is known about the regulation of stone cell formation at the transcriptomic, proteomic, and metabolomic levels. In the present study, we performed phenomic analysis on the stone cells and their associated vascular bundles distributed near the fruit cores. Transcriptomic, proteomic, and metabolomic analyses revealed a significant positive regulation of biological processes which contribute to the lignification and lignin deposition in stone cells near the fruit core, including sucrose metabolism and phenylalanine, tyrosine, tryptophan, and phenylalanine biosynthesis. We found many metabolites generated from the phenylpropanoid pathway contributing to the cell wall formation of stone cells near the fruit core. Furthermore, we identified a key transcription factor, PbbZIP48, which was highly expressed near the fruit core and was shown to regulate lignin biosynthesis in stone cells. In conclusion, the present study provides insight into the mechanism of lignified stone cell formation near the pear fruit core at multiple levels. Significance Statement: We provide new insights into understanding the mechanism of lignified stone cell formation near the pear fruit core at multi‐omics levels.